Odpowiedź :
1/2x - 2y = 8 | *2
2x+5y = 6
x - 4y = 16
2x+5y= 6
x= 16 + 4y
2*(16+4y) = 6
x= 16 + 4y
32+ 8y= 6
x= 16+4y
8y= 6- 32
x= 16 +4y
8y= -26|:8
x= 16 +4y
y= 3,25
x= 16+ 4 * 3,25
x= 13
y=3,25
2x+5y = 6
x - 4y = 16
2x+5y= 6
x= 16 + 4y
2*(16+4y) = 6
x= 16 + 4y
32+ 8y= 6
x= 16+4y
8y= 6- 32
x= 16 +4y
8y= -26|:8
x= 16 +4y
y= 3,25
x= 16+ 4 * 3,25
x= 13
y=3,25
(1/2)*x -2y = 8
2x + 5y = 6
-------------------
Z I) mamy 2y = (1/2)x - 8
y = (1/4)x - 4
2x + 5*[ (1/4)x - 4] = 6
2x + (5/4)*x - 20 = 6
(8/4)*x +(5/4)*x = 26
(13/4 )*x =26
13x = 104
x =104 /13 = 8
y = (1/4)*8 - 4 =2 - 4 = -2
Odp. x = 8 oraz y = -2
2x + 5y = 6
-------------------
Z I) mamy 2y = (1/2)x - 8
y = (1/4)x - 4
2x + 5*[ (1/4)x - 4] = 6
2x + (5/4)*x - 20 = 6
(8/4)*x +(5/4)*x = 26
(13/4 )*x =26
13x = 104
x =104 /13 = 8
y = (1/4)*8 - 4 =2 - 4 = -2
Odp. x = 8 oraz y = -2
1/2x-2y=8/*2
2x+5y=6
x-4y=16
2x+5y=6
x= 16+4y
2(16+4y)+5y=6
x=16+4y
32+8y+5y =6
x=16+4y
13y=-26
x=16+4y
y=-2
x=16+4*-2
y=-2
x=8
y=-2
2x+5y=6
x-4y=16
2x+5y=6
x= 16+4y
2(16+4y)+5y=6
x=16+4y
32+8y+5y =6
x=16+4y
13y=-26
x=16+4y
y=-2
x=16+4*-2
y=-2
x=8
y=-2